NU: Pergumulan Islam dan ABRI di Masa Kontemporer - J.H. Meuleman (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 1997)
The following article offers a review of a recent book bu Andree Feillard, followed by an extensive summary. This abstract will present the main points of the review.During the long period she lived in Indonesia, the attention of the French researcher and journalist, Andree Feillard, was particularly attracted to the large Indonesian traditionalist Muslim movement, the Nahdatul Ulama (NU). This is the main object of the book under review, whose title in English translation is